Effects of work-related factors on self-reported smoking among female workers in call centers: a cross-sectional study - Yang, Young Joon; Moon, Young Hoon; Do, Sang Yoon; Lee, Chul Gab; Song, Han Soo (Annals of occupational and environmental medicine, 2019)
This study conducted to investigate work-related factors in relation to smoking among women working in call centers in Gwangju, South Korea. From 56 call centers (7320 employees), we selected 10 and conducted a survey using a structured questionnaire by randomly selecting 10% of workers from each center. A total of 387 subjects participated in this survey We analyzed for 375 respondents, after excluding men and those with missing responses. We analyzed the relationships of work-related factors such as emotional labor, workplace violence, employment type, annual salary, working hours, employment period with smoking, using multiple logistic regression analysis. Emotional labor and workplace violence were measured using the Korean Emotional Labor Scale (K-ELS) and Korean Workplace Violence Scale (K-WVS). The prevalence of current smoking among call center female workers was 13.6%. Univariate analysis showed that "Emotional disharmony and hurt", "Experience of psychological and sexual violence from supervisors and co-workers" among items of K-ELS and K-WVS, working hours, annual salary correlated with smoking. After adjusting for emotional labor, workplace violence, employment type, annual salary, working hours, employment period, and age, only working hours show a significant association with smoking. Women who worked 40-49 h had 3.50 times (95% CI = 1.04-11.80) and worked more than 50 h had 8.68 times (95% CI = 1.89-39.78) greater odds of smoking as compared with women who worked less than 40 h. Smoking was associated with working hours among female workers in call center. However, emotional labor and workplace violence did not show significant relationships with smoking.